Learning to Use Evidence in Elementary School Over Time: A Study of the Discursive Construction of Ways of Answering Questions in Science Lessons - Luiz Gustavo Franco (Revista Brasileira de Pesquisa em Educação em Ciências, 2017)
The use of evidence in science lessons has been considered an important practice to be developed in science education. In this study, we investigate how 3rd graders constructed discursively the practice of using evidence. The theoretical and methodological framework of the study was grounded in Microethnography and Interactional Etnography. We characterize “ways of doing” related to evidence use based on the use of discursive resources: words/expressions that were emphasized by the participants in face-to-face interactions, through contextual cues of speech, such as intonation/volume shifts and pausing moments. We indicate how these ways of doing have changed over time and how participants negotiated a shared model in building answers using evidence. We also discuss methodological implications for research in Argumentation in science education and for classroom practice.